Transcranial Focused Ultrasound Stimulation Changes Brain Amyloid Load in Alzheimer's Disease - Kim, Jaeho; Kim, Kyeonghwan; Kum Jeungeun; Kim, Hyungmin; Kim, YoungSoo (2024 대한치매학회 추계학술대회 학술자료집, 2024)
Background & Objective: The accumulation of β-amyloid is recognized as the earliest pathological hallmark of Alzheimer's disease, initiating a cascade of neurodegenerative processes and cognitive decline. While recent advances have led to the development of anti-amyloid therapies as potential treatments for Alzheimer’s, their feasibility is limited by concerns over long-term stability and cost-effectiveness. Emerging research has demonstrated the safety and neuromodulatory potential of low-intensity ultrasound in the brain, positioning it as a relevant tool alongside other neuromodulation techniques such as transcranial electrical stimulation and transcranial magnetic stimulation. Methods: Ultrasound transducers were implanted on the skulls of 5xFAD mice to apply focused ultrasound stimulation (FUS). Five 5xFAD mice received low-intensity ultrasound stimulation for two weeks (5 days per week, 30 minutes per session) in vivo during awake stimulation. Blood Ab42 levels and brain amyloid plaque load were measured and compared to control. Results: FUS treatment resulted in a reduction in both the total number and size of amyloid plaques, along with an increase in plasma Ab42 concentrations. No brain hemorrhage or significant changes in GFAP levels were observed. Conclusion: Transcranial Focused Ultrasound Stimulation appears to be a safe and effective method for modulating brain amyloid load and holds potential for therapeutic application in Alzheimer’s disease patients.